Vacuum-assisted wound closure in vascular surgery – clinical and cost benefits in a developing country - Končar, Igor B; Cvetković, Slobodan; Dragaš, Marko; Pejkić, Sinisa; Lazović, Goran; Banzić, Igor; Zuvela, Marinko; Marković, Miroslav; Davidović, Lazar (Vojnosanitetski pregled, 2017)
Background/Aim. Surgical and chronic wounds in vascular patients might contribute to limb loss and death. Vacuum-assisted closure (VAC) – Kinetic Concepts, Inc. (KCI), has been increasingly used in Western Europe and the USA clinical practice for 15 years. Advantages of this method are faster wound healing, wound approximation, lower wound related treatment costs and improved quality of life during treatment. Evidence related to the usage of VAC therapy in vascular patients and cost effectiveness of VAC therapy in a developing country are lacking. The aim of this study was to explore results of VAC therapy in vascular surgery comparing to conventional methods and to test cost effects in a developing country like Serbia. Methods. All patients with wound infection or dehiscence operated at the tertiary vascular university clinic in the period from January 2011 – January 2012, were treated with VAC therapy. The primary endpoint was wound closure, while secondary endpoints were hospital stay, the number of weekly dressings, costs of wound care, working time of medical personnel. The patients were divided into groups according to the wound type and location: wound with exposed synthetic vascular implant (25%), laparotomy (13%), foot amputation (29%), major limb amputation (21%), fasciotomy (13%). The results of primary and secondary endpoint were compared with the results of conventional treatment during the previous year. Results. There was one death (1/42, 2.38%) and one limb loss (1/12, 2.38%) in the VAC group, and 8 deaths (8/38, 21.05%) and 5 (5/38, 13.15%) limb losses in the patients treated with conventional therapy. In the VAC group there was one groin bleeding (1/12, 2.38%), one groin reinfection (1/12, 2.38%) and one resistance to therapy with a consequent limb loss. Costs of hospital stay (p
Keywords: surgical wound infection; surgical wound dehiscence; vascular surgical procedures; vacuum; socioeconomic factors; treatment outcome